Complexity, Institutions and Public Policy: Agile Decision-making in a Turbulent World - and Room, Graham (Edward Elgar Pub, 2011)
Graham Room argues that conventional approaches to the conceptualization and measurement of social and economic change are unsatisfactory. As a result, researchers are ill-equipped to offer policy advice. This book offers a new analytical approach, combining complexity science and institutionalism. It also provides tools for policy makers in turbulent times. Part 1 is concerned with the conceptualization of socio-economic change. It integrates complexity science and institutionalism into a coherent ontology of social and policy dynamics. Part 2 is concerned with models and measurement. It combines some of the principal approaches developed in complexity analysis with models and methods drawn from mainstream social and political science. Part 3 offers empirical applications to public policy: the dynamics of social exclusion; the social dimension of knowledge economies; the current financial and economic crisis. These are supplemented by a toolkit for the practice of 'agile policy making'. This is a stimulating, provocative and highly original book. It will appeal to academics and students in social and policy studies and to a wide range of scholars in other disciplines where complexity science is already well-developed. It will also be of major interest for decision makers coping with complex and turbulent policy terrains.Contents: Preface 1. Introduction Part I: Concepts 2. The Complexity Paradigm 3. Complex Adaptive Systems 4. The Economy as a Complex Adaptive System 5. Institutional Settings and Architectures 6. Institutional Dynamics 7. The Struggle for Positional Advantage 8. Conceptualising Social Dynamics Part II: Methods 9. Attractors and Orbits in Dynamic Systems 10. Patterns in Time and Space 11. Connections and Networks 12. Mobility on Social Landscapes 13. Towards a Generic Methodology Part III: Policies 14. Agile Policy-Making 15. Poverty and Social Exclusion 16. Social Dynamics of the Knowledge Economy 17. Global Turbulence and Crisis Postscript: Tools for Policy-Makers References Index